Grupo Emergente IMIBIC-GE08 "Cuidados Enfermeros Integrales Perspectiva Multidisciplinar". Instituto Maimónides de Investigación Biomédica de Córdoba (IMIBIC). - López Soto, Pablo Jesús (Metas de Enfermería, 2020)
Brief presentation of the history of the IMIBIC-GE08 research group, "Comprehensive Nursing Care from a Multidisciplinary Perspective", from the Maimónides Institute for Biomedical Research, Cordoba, which speaks about 12 years of hard research work with one single reference: "Nursing Care", which entails implicitly a multidisciplinary approach, collaboration and translation. The scientific quality of the group can be observed in its promotion to Emerging Group in 2019; it was previously an associated group (IMIBIC-GA02), with an impact index of 52,604 in 2019, according to the Journal Citation Reports (JCR), in 150 publications, 92 of which had been indexed in JCR (in the 1st, 2nd, 3rd and 4th quartiles); and 22 (24%) among these were published in the first quartile and 10(10%) in the first decile. This group self-finances research conducted through different competitive processes, local, national or international, both in the public (university, Junta de Andalucía, Instituto de Salud Carlos III) and the private setting (Fundación MAPFRE). The group is formed by persons from different areas of knowledge: Nursing, Medicine, Social Work, Anthropology, etc. Specifically within healthcare professions, it includes Primary and Specialized Care. The lines of work are as diverse as person-centered nursing care. Among them, we can mention the papers on violence by intimate partner in healthcare professionals the chronobiological approach for different health conditions, domestic violence, lifestyle, occupational health, among other lines.